2021
DOI: 10.4018/ijgbl.2021070102
|View full text |Cite
|
Sign up to set email alerts
|

Can ESA Method Through Quizizz Games Enhance Vocabulary Knowledge?

Abstract: The teaching of vocabulary is essential in the world of teaching English as a foreign language (EFL). EFL learners have problems in learning vocabulary. To attract the students' attention, the teachers should have adequate teaching methods. One of the teachers' efforts to engage the students is by applying ESA (engage, study, and activate) through Quizizz to find out the enhancement of students' vocabulary knowledge. The study was done in a public junior high school. This was a quantitative research with a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Hence, this finding suggests that the applied treatment, namely the Quizizz app, stimulated the experimental group participants' performance compared to the control group. This study's results support previous studies that have found Arab World English Journal www.awej.org ISSN: 2229-9327 419 MGBL, particularly the Quizizz app, enhanced EFL vocabulary learning (BAL, 2018;Caroline & Grace, 2021;Huei et al, 2021;Katemba & Sinuhaji, 2021).…”
Section: The Effect Of Mobile Games On Efl Students' Vocabulary Acqui...supporting
confidence: 89%
See 1 more Smart Citation
“…Hence, this finding suggests that the applied treatment, namely the Quizizz app, stimulated the experimental group participants' performance compared to the control group. This study's results support previous studies that have found Arab World English Journal www.awej.org ISSN: 2229-9327 419 MGBL, particularly the Quizizz app, enhanced EFL vocabulary learning (BAL, 2018;Caroline & Grace, 2021;Huei et al, 2021;Katemba & Sinuhaji, 2021).…”
Section: The Effect Of Mobile Games On Efl Students' Vocabulary Acqui...supporting
confidence: 89%
“…By integrating the Quizizz platform with its gaming features, empirical studies on EFL learners found that the experimental groups who learned vocabulary via mobile games outscored their peers who used traditional teaching methods (BAL, 2018;Caroline & Grace, 2021;Huei, Yunus, & Hashim, 2021;Katemba & Sinuhaji, 2021). For example, Hui et al ( 2021) noted a significant improvement in the vocabulary repertoire of EFL students who used the Quizizz app based on pretest and posttest results.…”
Section: The Effect Of Mobile Games On Efl Students' Vocabulary Acqui...mentioning
confidence: 99%
“…One of the teachers' efforts to engage the students is applying ESA (engage, study, and activate). (Katemba & Sinuhaji, 2021) So, to verify the impact of online games, this study needed a wide range of data to analyze the results. Consequently, it was necessary to use mixed methods to gather qualitative and quantitative data information.…”
Section: Methodsmentioning
confidence: 99%
“…Also, there is a strong link between vocabulary knowledge and language learning. The value of vocabulary knowledge cannot be denied in comprehending and learning a second language (Katemba, 2021).…”
Section: Vocabulary Learningmentioning
confidence: 99%
“…During the COVID-19 pandemic, online games for language learning grew in popularity for teaching and learning English as a Foreign Language (EFL) (Katemba and Sinuhaji, 2021). One up-to-date method to teach vocabulary is through Kahoot!…”
Section: Introducationmentioning
confidence: 99%